Causal associations of gut microbiota and metabolites on sepsis: a two-sample Mendelian randomization study - Zhao, Jian; Pan, Xin; Hao, Di; Zhao, Yi; Chen, Yuanzhuo; Zhou, Shuqin; Peng, Hu; Zhuang, Yugang (Frontiers in Immunology, 2023)
Background: Sepsis stands as a dire medical condition, arising when the body's immune response to infection spirals into overdrive, paving the way for potential organ damage and potential mortality. With intestinal flora's known impact on sepsis but a dearth of comprehensive data, our study embarked on a two-sample Mendelian randomization analysis to probe the causal link between gut microbiota and their metabolites with severe sepsis patients who succumbed within a 28-day span.Methods: Leveraging data from Genome-wide association study (GWAS) and combining it with data from 2,076 European descendants in the Framingham Heart Study, single-nucleotide polymorphisms (SNPs) were employed as Instrumental Variables (IVs) to discern gene loci affiliated with metabolites. GWAS summary statistics for sepsis were extracted from the UK Biobank consortium.Results: In this extensive exploration, 93 distinct genome-wide significant SNPs correlated with gut microbial metabolites and specific bacterial traits were identified for IVs construction. Notably, a substantial link between Coprococcus2 and both the incidence (OR of 0.80, 95% CI: 0.68-0.94, P=0.007) and the 28-day mortality rate (OR 0.48, 95% CI: 0.27-0.85, P=0.013) of sepsis was observed. The metabolite α-hydroxybutyrate displayed a marked association with sepsis onset (OR=1.08, 95% CI: 1.02-1.15, P=0.006) and its 28-day mortality rate (OR=1.17, 95% CI: 1.01-1.36, P=0.029).Conclusion: This research unveils the intricate interplay between the gut microbial consortium, especially the genus Coprococcus, and the metabolite α-hydroxybutyrate in the milieu of sepsis. The findings illuminate the pivotal role of intestinal microbiota and their metabolites in sepsis' pathogenesis, offering fresh insights for future research and hinting at novel strategies for sepsis' diagnosis, therapeutic interventions, and prognostic assessments.